Supporting Similarity Queries in MARS - Ortega, Michael; Rui, Yong; Chakrabarti, Kaushik; Mehrotra, Sharad; Huang, Thomas S. (ACM Multimedia Conference, 1997)
To address the emerging needs of applications that require access to and retrieval of multimedia objects, we are developing the Multimedia Analysis and Retrieval System (MARS) in our group at the University of Illinois [13]. In this paper, we concentrate on the retrieval subsystem of MARS and its support for content-based queries over image databases. Content-based retrieval techniques have been extensively studied for textual documents in the area of automatic information retrieval [24, 21. This paper describes how these techniques can be adapted for ranked retried over image databases. Specifically, we discuss the ranking and retrieval algorithms developed in MARS based on the Boolean retrieval model and describe the results of our experiments that demonstrate the effectiveness of the developed model for image retrieval.